Cytotoxic and antibacterial activities of sesquiterpene lactones isolated from Tanacetum praeteritum subsp praeteritum - (:unkn) unknown (GEORG THIEME VERLAG KG, 1996)
Ten sesquiterpene lactones and one sesquiterpene isolated from Tanacetum praeteritum subsp. praeteritum: 1 alpha,6 alpha-dihydroxyisocostic acid methyl ester (2), 1 alpha-hydroxy-1-deoxoarglanine (3), douglanin (5), santamarin (6), reynosin (7), 1-epi-tatridin B (8), ludovicin A (10), armexin (12), armefolin (13), armexifolin (14), and 3 alpha-hydroxyreynosin (15) were tested against the human lung carcinoma cell line GLC(4) and the colorectal cancer cell line COLO 320 as well as against the bacteria Bacillus subtilis, Staphylococcus aureus, Proteus mirabilis, Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Enterococcus, beta-hemolytic Streptococcus, and the yeast Candida albicans. In addition, two germacranolides tatridin A (16) and tamirin (17) were included in the study. All compounds showed cytotoxic activity (IC50 = 124 mu M) but most of them were not effective in the antimicrobial tests.
Keywords: Tanacetum praeteritum subsp praeteritum; Asteraceae; sesquiterpene lactones; bioassay; cytotoxic activity; human colorectal cancer cell line; human small cell lung cancer cell line; antibacterial activity; CHILIOPHYLLUM VAR HEIMERLEI; BIOLOGICAL-ACTIVITIES